Fabrication of 2D Hetero-Complexes With Nucleic-Acid-Base Adenine and Fatty-Acid Stearic Acid at Liquid/Solid Interface - Zhao, Huiling; Yang, Qian; Wang, Zegao; Zhao, Hang; Liu, Bo; Chen, Qianming; Dong, Mingdong (Frontiers in Chemistry, 2019)
Designing and fabricating hetero-complexes composed of organic and biological compounds had become an exciting area referring to biological recognition, molecular devices etc. Here, hydrogen-bonded complex of nucleic-acid-base (adenine, A) and fatty-acid (stearic acid, SA) was designed, fabricated and investigated at liquid/solid interface. The interesting striped-shaped structure composed of SA-A-SA trimers was formed after introducing adenine molecules. Meanwhile, the primary lamella-shape characteristic of the assembly of SA molecules was kept because of the collaboration of non-covalent interactions of molecule-molecule and molecule-substrate. With a series of experimental characterization and theoretical simulation, the origination of the as-prepared 2D hetero-complexes was gradually exhibited from the assembled structures of two building blocks of stearic acid and adenine. Our study provides a blueprint for designing additional multi-component complexes based on the existing molecular assembled architectures.